IMPROVING STUDENTS’ READING COMPREHENSION BY USING SURVEY, QUESTION, PREDICT, READ, RESPOND, AND SUMMARIZE (SQP2RS) TECHNIQUE AT SMP NEGERI 7 GUNUNG TALANG - Alex Sandra (ELP (Journal of English Language Pedagogy), 2019)
Reading comprehension is one of the important aspects that must be mastered by students. Based on researcher’s experience and observation during teaching, it was found that most students got unsatisfactory scores under the minimum graduation criteria (KKM). This problem is caused by several factors including lack of knowledge in reading strategies, lack of ability to find information or ideas of the text being read. This research was Classroom Action Research. The main objective of this research was to explain how far the SQP2RS reading strategy (Survey, Question Predict, Read, Respond, and Summarize) can improve students’ reading comprehension and explain what factors influence the improvement of students' reading skill. This research was conducted in 2 cycles. Each cycle consisted of 4 meetings. It was done at eight grade students of SMPN 7 Gunung Talang. The data in this study were collected through tests, observations, field notes and interviews and each end of the cycle were given a test. In collecting data the researcher was assisted by an English teacher at the author's place as a collaborator. The findings in this study indicated that students' reading ability improved after using the SQP2RS strategy. The improvement was influenced by several factors, namely, material, media, class activities, classroom management, teacher strategies, and teacher approaches. Therefore it can be concluded that the use of the technique SQP2RS can improve students’ reading comprehension.